2022
DOI: 10.1039/d2ra02988j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, magnetoresistance and spin filtering in graphene|2 monolayer-CrI33|graphene van der Waals magnetic tunnel junctions

Abstract: We investigate the structural configuration, electronic structure and spin-polarized quantum transport of graphene|2 monolayer-CrI3|graphene heterostructure with Ag(111) layers as the electrode, using density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Even though the previous theoretical studies revealed the hybridization of the CrI 3 /graphene interface, its impacts on the magnetic coupling have not been well understood. [ 30–32,34 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the previous theoretical studies revealed the hybridization of the CrI 3 /graphene interface, its impacts on the magnetic coupling have not been well understood. [ 30–32,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Even though the previous theoretical studies revealed the hybridization of the CrI 3 /graphene interface, its impacts on the magnetic coupling have not been well understood. [30][31][32]34] To gain a detailed understanding and a deeper insight into the proximity effect, we performed first-principles calculations based on density functional theory. [43][44][45] The results of the interlayer exchange interaction (J inter ) are presented in Figure 4d.…”
Section: Electric Controls Of the Spin-selective Memtransistormentioning
confidence: 99%
See 1 more Smart Citation
“…1(e) caused by inherent electronic characteristics and interface splice. 62,63 So the central edge states in Fig. 7(a) can easily pass through the center in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various 2D in-plane and van der waals (vdw) heterostructures have been explored in the quest of achieving a high TMR and a decimated power consumption. For example, the first principle calculation of vdw heterostructures such as Co/ MoS2/graphene/MoS2/Co [37] and Au/graphene/2 monolayer of CrI3/graphene/Au [38] have predicted to engender a TMR of 1270% and 2 × 10 4 % respectively. On the other hand, ab initio calculations of in-plane heterostructures like VS 2 /MoS 2 /VS 2 have revealed a TMR of 4 × 10 3 % [39].…”
Section: Introductionmentioning
confidence: 99%